Shedding light on the darker side of language: A dialogical approach to cross-cultural collaboration. (April 2017) - Beeler, Betty; Lecomte, Philippe
The purpose of this article is to shed light on the "darker" side of language in cross-cultural communication and explore ways that it can be addressed, using a dialogical approach. Bakhtin's dialogical perspective conceptualizes sensemaking as the co-construction of meaning through interconnected utterances ("addressivity" and "responsivity"), multivoicedness ("polyphony"), and multiple speaking styles ("heteroglossia"). We use these concepts to analyze the social processes underlying linguistic hegemony and language-based in-group behavior in a case study of the performance of six multicultural teams at an American subsidiary in France. We found that although dialogical practices proved to be effective in deterring the emergence of the dark side of language, the lack of a dialogical mindset prevailed in four of the six teams. These findings point to the need for cross-cultural management policies which reward addressivity, polyphony, and heteroglossia while penalizing team members who use their superior language skills to dominate others.